Assessment of consultation impact on emergency department operations through novel metrics of responsiveness and decision-making efficiency. Issue 3 (May 2014) - Lee, Patricia A.; Rowe, Brian H.; Innes, Grant; Grafstein, Eric; Vilneff, Renee; Wang, Dongmei; van Rheenen, Susan; Lang, Eddy
ABSTRACT: Objectives: Requests for specialty consultation are common in emergency departments (EDs) and often contribute to delays in throughput. Our objectives were to describe the contribution of the consultation process to total ED length of stay (LOS) through novel metrics and illustrate causes of delay. Methods: We conducted a prospective cross-sectional study at three Canadian tertiary care centres. Adult ED patients with requested medical/surgical consultations were enrolled. We created original metric intervals: total consultation time (TCT) defined as the interval from the initial consultation request to the disposition decision, consult response time (CRT) from the request to the consultant arrival, and decision-making interval (DMI) from arrival to the disposition decision. The consultation impact index (CII) was defined as the percentage of ED LOS consumed by the TCT. Reasons for delay were documented if time stamps exceeded preset benchmarks. Results: The median TCT for 285 patients was 138 minutes (interquartile range [IQR]: 82–239 minutes), whereas the median total ED LOS was 778 minutes (IQR 485–1, 274 minutes). The median CRT was 55 minutes (IQR 21–115 minutes), and the median DMI was 58 minutes (IQR 25–126 minutes). The CII measured 26% (95% CI 23–28). Major contributors to consultation delay included urgent ward issues, simultaneous ED consultations, and the need for additional laboratory or radiographic investigations. Conclusion: The consultation process is highly variable and has an important impact on ED LOS. We describe novel measures related to consultation performance and provide an analysis of what causes delays. These results can be used to seek improvements in the consulting process.